A Feasibility Study on the Establishment of J-Larn Tattoo at #89 Brgy. San Agustin Susano Road, Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Tattoo is continuously growing its popularity in the Philippines. The researchers came up with this feasibility study of a tattoo business. The researchers conducted the survey to people who are 18 years old and above at Bgry. San Agustin,Susano Road, Novaliches, Quezon City. A total of 100 respondents were taken for the study. The survey has seven (7) questions with options and check list. Respondents were also asked if they would recommend tattoo service to friends. The results of survey showed that 71% are interested with tattoo. Respondents interested on henna is 62% and 38% on permanent tattoo. The tattoo they prefer is colored which is 51% and 49% for black and white. For booking of the schedule for tattoo, most of the respondents prefer walk at 50%, while 37% prefer online and 13% prefer on-call reservations for the service. Preference on advertisement through social media is 49%, tarpaulin 35% and sticker 5%. Also, 33% of the respondents want to have tattoo on the shoulder, 32% on the arms, 21% on their feet and 14% on their back. The location at #89 Brgy. San Agustin, Susano Road, Novaliches, Quezon City was agreed to be accessible by 73% of the respondents. J-LARN Tattoo came up with a feasible business that offers services of permanent and henna tattoo to people age 18 years old and above. Prices will vary depending on the size difficulties of design and part where tattoo is to be drawn. Competitive pricing strategy was used by the researchers. The activities that will promote the business are seminars and event programs with tattoo artists. The business is located at #89 Brgy. San Agustin, Susano Road, Novaliches, Quezon City while promotional activities are focused on social media through facebook and instagram, flyers and tarpaulins. The business aims to provide services which allows self-expression through art of tattoo.
Keywords: feasibility study, tattoo, permanent tattoo, henna tattoo